Achievement of Remission in Two Early Rheumatoid Arthritis Cohorts Implementing Different Treat‐to‐Target Strategies. Issue 7 (28th May 2020) - Norvang, Vibeke; Brinkmann, Gina H.; Yoshida, Kazuki; Lillegraven, Siri; Aga, Anna‐Birgitte; Sexton, Joseph; Tedeschi, Sara K.; Lyu, Houchen; Norli, Ellen S.; Uhlig, Till; Kvien, Tore K.; Mjaavatten, Maria D.; et al.
Abstract : Objective: The objective of this study was to compare achievement of remission in 2 early rheumatoid arthritis (RA) treat‐to‐target (TTT) cohorts, a tight control cohort with a target of stringent remission in a randomized controlled trial and an observational cohort targeting a looser definition of remission in clinical practice. Methods: We analyzed data from the Aiming for Remission in Rheumatoid Arthritis: a randomised trial examining the benefit of ultrasound in a Clinical Tight Control regimen (ARCTIC) trial and the Norwegian Very Early Arthritis Clinic (NOR‐VEAC) observational study. Both were Norwegian multicenter studies that included disease‐modifying antirheumatic drug (DMARD)–naive RA patients and implemented TTT. The target in the ARCTIC trial was remission defined as a Disease Activity Score (DAS) of <1.6 plus 0 swollen joints on a 44‐joint count, while the target in the NOR‐VEAC study was the less stringent remission target of a DAS28 of <2.6. We assessed achievement of the study‐specific targets and compared the odds of achieving the American College of Rheumatology(ACR)/European League Against Rheumatism (EULAR) Boolean remission during 2 years of follow‐up. Results: We included 189 patients from the ARCTIC trial and 330 patients from the NOR‐VEAC study. The study‐specific target had been achieved in more than half of the patients in each cohort at 6 months, increasing to >60% at 12 and 24 months. The odds of achieving ACR/EULAR Boolean remission during follow‐up were higher in the ARCTIC trial than in the NOR‐VEAC study, with significant differences at 3 months (odds ratio 1.73 [95% confidence interval 1.03–2.89]), 12 months (odds ratio 1.97 [95% confidence interval 1.21–3.20]), and 24 months (odds ratio 1.82 [95% confidence interval 1.05–3.16]). Conclusion: A majority of patients in both cohorts reached the study‐specific treatment targets. More patients in the ARCTIC trial than in the NOR‐VEAC study achieved ACR/EULAR Boolean remission during follow‐up, suggesting that targeting a more stringent definition of remission provides further potential for favorable outcomes of a TTT strategy.